New Middle Eocene proboscidean from Togo illuminates the early evolution of the elephantiform-like dental pattern. Issue 1960 (13th October 2021) - Hautier, Lionel; Tabuce, Rodolphe; Mourlam, Mickaël J.; Kassegne, Koffi Evenyon; Amoudji, Yawovi Zikpi; Orliac, Maëva; Quillévéré, Frédéric; Charruault, Anne-Lise; Johnson, Ampah Kodjo Christophe; Guinot, Guillaume
Abstract : Africa has played a pivotal role in the evolution of early proboscideans (elephants and their extinct relatives), yet vast temporal and geographical zones remain uncharted on the continent. A long hiatus encompassing most of the Eocene (Ypresian to the Early Priabonian, around 13 Myr timespan) considerably hampers our understanding of the early evolutionary history of the group. It is notably the case with the origin of its most successful members, the Elephantiformes, i.e. all elephant-like proboscideans most closely related to modern elephants. Here, we describe a proboscidean lower molar discovered in Lutetian phosphate deposits from Togo, and name a new genus and species, Dagbatitherium tassyi . We show that Dagbatitherium displays several elephantiform dental characteristics such as a three-layered Schmelzmuster, the presence of a mesoconid, transversely enlarged buccal cusps and the individualization of a third lophid closely appressed to a minute distal cingulid. Dagbatitherium represents a stem Elephantiformes, pushing back the origin of the group by about 10 Myr, i.e. a third of its currently known evolutionary history. More importantly, Dagbatitherium potentially unlocks the puzzle of the origin of the unique elephantiform tooth crown organization by bridging a critical temporal and morphological gap between early bunodont incipiently bilophodont proboscidean taxa and more derived elephantiforms.